Toward arbitration between subnational units and foreign investors? - Charles-Emmanuel Côté (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2015)
The ICSID Convention has envisaged arbitration between subnational units and foreign investors since its inception in 1966, but no such unit has ever been party to ICSID arbitration. The recent ratification of the Convention by Canada could trigger the emergence of this new sort of arbitration, bringing international investment law into unchartered territory.
Keywords: 330